(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
On the 13th of November 2015, Dr Chris Sarra delivered a groundbreaking lecture to the Australian Senate on Indigenous policy. In that lecture, Sarra tells us how, the then Prime Minister, Malcom Turnbull had asked him to list three things the government could do to make a difference in the Indigenous policy space. Sarra admits here that he was somewhat distracted by the fact that it was the day of the NRL Grand Finals and his beloved Cowboys were playing the Broncos, but he did promise to get back to the PM, and he did so with the following three points, which have since become known as the ‘Sarra Trilogy’. They are Acknowledge, embrace and celebrate the humanity of Indigenous Australians. Bring us policy approaches that nurture hope and optimism rather than entrench despair. Do things with us, not to us! In what follows, we first give a short summary of our philosophical and methodological orientation. Then we will proceed with a commentary on each of the elements of Dr Sarra’s Trilogy, which we will argue constitutes a relational and policy manifesto that marks a vital and necessary departure from current policy settings.